The Impact of Non-Performing Financing (NPF) to Profitability (Return On Equity) at Sharia Bank in Indonesia - Muksal, Muksal (European Journal of Islamic Finance, 2018)
This study aims to analyze the effect of Non Performing Financing (NPF) on Profitability proxy with Return On Equity (ROE) variable of syariah bank in Indonesia period of 2013-2015. The sample population in this study were three banks with sample selection using purposive sampling technique with syariah bank criteria which published periodic financial statements during the observation period that is the period of 2013-2015. The research data is quantitative data obtained from the quarterly financial report of sharia bank. Data analysis using simple linear analysis with 5% significance level which aims to obtain how the overall influence of the relationship between NPF variable and Return on Equity (ROE). The results showed that the variable Non Performing Financing (NPF) has a negative and significant effect on Return On Equity (ROE) with a value t greater than 0.005. High NPF ratio in syariah bank can give a picture of the negative effect on profitability of sharia bank